Medical cannabis: From research breakthroughs to shifting public perceptions and ensuring safe use - Muhammad Kamal Hossain; Han Jung Chae (Integrative Medicine Research)
Background: This review aimed to examine the recent breakthroughs in medical cannabis research, explore the shifting public perceptions and the stigma associated with its use and discuss strategies for enhancing the safety of medical cannabis. Methods: We reviewed literature on medical cannabis and also synthesized the connections between scientific research, public perception and safety considerations in the uses of medical cannabis, providing a comprehensive understanding of how these elements influence each other and shape the future of medical cannabis use for patient adherence. Results: The landscape of medical cannabis has evolved dramatically over the past few decades. The transition from prohibition to medical recognition is shaped by complex interactions among scientific advancements, public perception and regulatory frameworks for its legalization. Conclusions: Medical cannabis is now recognized for its potential therapeutic benefits, supported by an expanding body of scientific research. The future of medical cannabis is shaped by the interplay between scientific research, public perception, and safety considerations which forms a feedback loop.